Bytový dům - Švestka, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Předmětem bakalářské práce je vypracování projektové dokumentace pro provedení stavby bytového domu v městské části Brno-Komárov. Objekt je samostatně stojící s pěti nadzemními a jedním podzemním podlažím. V suterénu se nachází podzemní garáže a technické zázemí objektu. V nadzemních podlažích se nachází 25 bytů, o dispozici 1KK, 2KK a 4KK. Byty v 1.NP na jihovýchodní straně mají samostatné předzahrádky. Byty v nadzemních podlažích disponujíc samostatnými lodžiemi. Součástí objektu je 25 parkovacích stání, venkovní parkoviště a stání pro popelnice. Objekt je zateplen kontaktním zateplovacím systémem ETICS. Zastřešení tvoří vegetační a pultová střecha.

The subject of the bachelor thesis is the preparation of project documentation for the construction of a residential building in the Brno-Komárov district. The building is detached with five above-ground and one underground floor. In the basement there are underground garages and technical background of the building. There are 25 apartments on the above-ground floors, with 1KK, 2KK and 4KK. The apartments on the 1st floor on the southeast side have separate front gardens. The apartments on the upper floors have separate loggias. The building includes 25 parking spaces, outdoor parking and a parking space for bins. The building is insulated with ETICS contact insulation system. The roofing consists of a vegetated and pitched roof.
Apartment building
Keywords: Bytový dům; novostavba; vegetační střecha; iso-nosník; ETICS; monolitický strop; vápenopískové zdivo; Residential building; new building; vegetated roof; iso-beam; ETICS; cast-in-place reinforced concrete floor; calcium-silicate masonry